Dermatitis artefacta. - Reis, M D; Barbosa, A; Matildes, J; Freitas, J P; Rodrigo, F G (Acta Médica Portuguesa, 1997)
We report a case of a 29-year-old man presenting skin ulcerations on both sides of the mandible. The diagnosis of dermatitis artefacta was based on the morphology and evolution of the lesions, on the patient's borderline personality, on the objects found in his possession, and a later admission of having an involvement in the aggravation of the lesions.